ĀPATTI FROM THE PERSPECTIVE OF PENOLOGY - Champathong, Somchai; Tansrisook, Sompornnuch (Journal of Buddhist Studies Chulalongkorn University, 2022)
This research article aims to study the monastic punishment in the Vinaya and the Commentary from the perspectives of two penological theories – deterrence theory and rehabilitative theory – as well as to analyze the relationship between the monastic offense and the five parts of Buddhism, i.e. the monastic community, the perpetrating monk, other monks, laypeople, and the religion, according to the Buddha’s objectives in the legislation of monastic orders. The research found that the three categories of monastic punishment – expulsion from monkhood, probation, and confession – are consistent with the principles of both penological theories. From the perspective of deterrence theory, punishments undermine future opportunities, are of great inconvenience, and disgrace the perpetrator, respectively. From the perspective of rehabilitative theory, the punishments are expulsion from monkhood in order to remain in a different but more appropriate status, exclusion from monkhood for correction, and expression of penitence. Apatti can be considered either as deterrence or rehabilitation, depending on the conscience of the perpetrating monk. It is deterrence for remorseless monks so that they may be law-abiding, while it is rehabilitation for those who are well-behaved to liberated ones who have attained the spiritual goal. The 5 parts of Buddhism are stakeholders in monastic offense and play a role in monks’ following of disciplinary rules and control of sense-faculties. The study shows that monastic punishments are self-correction of the wrongdoing. Having committed an offense, a monk should admit it and join the process of correction as soon as he realizes it.